2015
DOI: 10.1520/acem20150012
|View full text |Cite
|
Sign up to set email alerts
|

Superabsorbent Polymers as a Means of Improving Frost Resistance of Concrete

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Similarly, the pore structure of concrete mixed with various types of SAPs and the freeze–thaw resistance of concrete containing SAPs have been studied [11]. Freeze–thaw resistance tests for concrete have been conducted by setting the SAP dosage and SAP particle size as variables [12]. Recently, the effect of two types of SAPs on the freeze–thaw resistance of concrete in various regions of the world has been reported via the results of an inter-laboratory study [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the pore structure of concrete mixed with various types of SAPs and the freeze–thaw resistance of concrete containing SAPs have been studied [11]. Freeze–thaw resistance tests for concrete have been conducted by setting the SAP dosage and SAP particle size as variables [12]. Recently, the effect of two types of SAPs on the freeze–thaw resistance of concrete in various regions of the world has been reported via the results of an inter-laboratory study [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies have found that SAP improves the freeze–thaw resistance of concrete [11,12,13,14,15]; however, opposite cases have also been reported [13,14,16]. A possible explanation for these conflicting results could be the complex absorption behavior of SAPs in hardened concrete when the concrete is exposed to water.…”
Section: Introductionmentioning
confidence: 99%
“…Superabsorbent polymer hydrogel particles provide an effective method of internal curing [14][15][16][17], because the hydrogel particles can absorb and release large amounts of water to fuel the hydration reaction [13]. The use of hydrogel particles for internal curing has been found to reduce autogenous shrinkage [17][18][19][20][21][22][23][24], reduce crack propagation [9,25,26], increase autogenous sealing potential [9,27,28], increase resistance to freeze-thaw cycles [29][30][31][32][33][34], and increase durability [33,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…This fact influences the method of calculating the water-binder ratio. Usually, with respect to concrete composites with SAP addition, three variants of this coefficient are distinguished: (w/c) tot —total water-binder ratio, (w e /c)—ratio of entrained water to the mass of the binder and (w eff /c)—effective water-binder ratio, where w eff is the total mass of water used in the concrete mix, minus the mass of water entrained in the modifier serving as the internal curing agent [ 6 , 39 ].…”
Section: Introductionmentioning
confidence: 99%